SOCIOCULTURAL ASPECTS IN KARL POPPER'S PHILOSOPHY IN THE CONTEXT OF MODERN EDUCATION - Azamatova, Gulrukh (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In this article, the author explores the philosophy of Karl Popper through its socio-cultural implications for modern education. Using the Popperian criteria of critical rationalism and the concept of an open society, as well as his method of social engineering, the author demonstrates the significance of these ideas for the transformation of education and pedagogy in modern times.